Considering risk of cascading line outages in transmission expansion planning by benefit/cost analysis. (June 2016) - Karimi, Ebrahim; Ebrahimi, Akbar
Highlights: Including blackouts risk caused by cascading transmission line outages in the TEP. A practical way for choosing more effective policies for reliability improvement. To show it is better to plan for suppressing cascades as fast as possible. Abstract: It has been shown that large blackouts happen more likely than may be expected. Recent investigations revealed that cascading outages are the major cause of power system blackouts. Therefore, risk of cascading outages must be considered in the planning and operating procedures. In this paper a novel procedure is proposed for transmission expansion planning (TEP) by using the ORNL–Pserc–Alaska (OPA) model. Some improvements are introduced to this model for choosing more effective candidate transmission lines to be used in TEP regarding risk of cascading outages. A nonlinear estimation is used to assess the consequences of blackouts after cascading transmission line outages. The power law as a fingerprint of self-organized criticality in power systems is used to calculate the likelihood of blackouts. The benefit of each policy to expand the transmission system is derived from risk assessment and the best one is picked out using benefit/cost analysis. The simplicity of the proposed method makes it appropriate in real life. The proposed method is applied to test systems to investigate its applicability. The results provide motivation for considering the risk of cascading line outages in TEP that afford substantial saving to society.